Kandungan Protein dan Uji Kesukaan Bronis Krispi dengan Substitusi Tepung Edamame (Glycine max (L.) Merrill) dan Hidrolisat Protein Ikan Tuna: Protein Content and Preferred Test of Crispy Brownies with Substitution of Edamame Flour (Glycine max (L.) Merrill) and Tuna Protein Hydrolisates (Thunnus sp) - Farida Wahyu Ningtyias; Shafa Aqila Putri Ramadani; Septi Nur Rachmawati (Amerta Nutrition, 2026)
Background: Malnutrition among school-age children is closely linked to dietary patterns. Crispy brownies can serve as a high-protein snack through the substitution of edamame flour and tuna protein hydrolysate. Edamame and tuna are nutrient-dense and readily available in Jember Regency, yet their use in school snacks remains limited. Objectives: This study aimed to analyze the protein content and conduct a preference test of crispy brownies substituted with edamame flour and tuna protein hydrolysate. Methods: This quasi-experimental study utilized four crispy brownies formulas: X0 (100%:0%:0%), X1 (70%:27.5%:2.5%), X2 (70%:25%:5%), and X3 (70%:22.5%:7.5%) for wheat flour, edamame flour, and tuna protein hydrolysate respectively. The organoleptic test involved 30 untrained panelists. Protein analysis was conducted at the RPHP and KBHP FTP Laboratories, University of Jember. Protein data were analyzed using Kruskal–Wallis, while the preference test used Friedman. Results: The protein content of the crispy brownies per 100 g was 9.87, 13.17, 13.55, and 13.89 g, respectively. The highest color preference was for X3, while the highest aroma, taste, and texture preferences were for X0. Based on the exponential comparison method, the best formula was X3 with 13.89 g/100 g protein or 0.69 g per piece (5 g). Conclusions: Substituting edamame flour and tuna protein hydrolysate increased the protein content and affected the taste, aroma, and texture of crispy brownies, but did not have a significant effect on color.